2017
DOI: 10.1136/bcr-2017-222077
|View full text |Cite
|
Sign up to set email alerts
|

All sorts of tests, only one question: an unexpected cause of hypertension

Abstract: A 48-year-old woman presented to the Accident and Emergency department with a 4 month history of headaches, nausea and dizziness. She was found to have severe hypertension and hypokalaemia. Extensive investigations did not find any secondary cause for hypertension. The patient was discharged with oral doxazosin therapy which controlled the blood pressure. Before the follow-up appointment at the hypertension clinic, the patient and her husband identified that her headaches coincided with liquorice tea consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…9 The glycyrrhetinic acid present in the plant is believed to be responsible for this action. Foster S et al 10 reported a case of a patient with persistent hypertension with no apparent cause, which was later attributed to consumption of Liquorice tea, which coincided with each episode of symptoms of hypertension. On stopping intake of Liquorice tea, the patient turned normal.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…9 The glycyrrhetinic acid present in the plant is believed to be responsible for this action. Foster S et al 10 reported a case of a patient with persistent hypertension with no apparent cause, which was later attributed to consumption of Liquorice tea, which coincided with each episode of symptoms of hypertension. On stopping intake of Liquorice tea, the patient turned normal.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%